Breath of Recovery: Unraveling the Spirometric Secrets of Post-COVID Resilience (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Abstract not availableJ Bangladesh Coll Phys Surg 2025; 43: 3-4